Alveolar Hemorrhage, a Rare and Life-Threatening Complication of Catastrophic Antiphospholipid Syndrome - Grace Loza; Carlos Hallo; Byron Chiliquinga; Alejandro Hallo (Case Reports in Rheumatology)
Alveolar hemorrhage is the rarest pulmonary complication of catastrophic antiphospholipid syndrome and is associated with high mortality risk. This life-threatening complication results from autoimmune damage to the alveolar blood vessels. Given the limited literature addressing the association of these two pathologies, we report a series of three cases with this complication and then compare our findings with 6 cases reported in the literature.